EXPLORATION OF STOMATA TYPES OF SHADE TREES AT UIN RADEN MAS SAID: A CONTEXTUAL LEARNING RESOURCE ON PLANT STRUCTURE AND DEVELOPMENT - Salsabila, Nauroh Aisy; Lararassati, Sisil; Anggrella, Dita Purwinda (Universitas Negeri Yogyakarta, 2025)
Stomata are important structures on the leaf surface that function to regulate gas exchange and water loss in plants. Students often experience misconceptions about the relationship between plant structure and function because the learning resources used tend to be text-based without the support of contextual examples or direct observation. This study aims to identify the types of stomata in three types of shade trees within the UIN Raden Mas Said environment, serving as contextual learning resources for plant structure and development. This type of research is descriptive qualitative. The materials used include ketapang leaves (Terminalia catappa), pulai leaves (Alstonia scholaris), and breadfruit leaves (Artocarpus altilis), as well as distilled water. Observations were made under a light microscope at 100× and 400× magnification. The observation data were analysed descriptively by comparing the characteristics of the stomata found in the three species with those of stomata types in the literature. Observations show that ketapang (Terminalia catappa) and breadfruit (Artocarpus altilis) leaves have anomocytic stomata, while pulai (Alstonia scholaris) leaves have anisocytic stomata. These findings provide stomatal morphology data that can be used as locally based teaching materials to enhance students' connections between botanical concepts and their environment.